2018
DOI: 10.1590/1678-5150-pvb-5208
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of the cerebral ventricles of healthy domestic cats

Abstract: RESUMO.-[Alterações senis dos ventrículos cerebrais de gatos domésticos hígidos.] O estudo objetivou a determinação das alterações senis dos ventrículos cerebrais de gatos domésticos hígidos não braquicefálicos pela aquisição de imagens encefálicas de 12 indivíduos adultos (1 a 6 anos), 11 maduros (7 a 11 anos) e 10 geriátricos (12 anos de idade ou mais) por ressonância magnética. Nossa hipótese é de que o sistema ventricular dos gatos se expande com o avanço da idade. A possibilidade de evidenciação das cavid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In fact, the animals involved in this work are all adult sheep of 18-24 months old. However, no indications about changes in the brain indexes in the sheep are available, but it is reasonable to argue that differences related to age groups can be found, as occur in humans and in animals such as cat [32] and dog [33]. Russel et al [5] reported changes in the sheep brain volume as increments between 3 and 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the animals involved in this work are all adult sheep of 18-24 months old. However, no indications about changes in the brain indexes in the sheep are available, but it is reasonable to argue that differences related to age groups can be found, as occur in humans and in animals such as cat [32] and dog [33]. Russel et al [5] reported changes in the sheep brain volume as increments between 3 and 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a previous publication, which found a positive correlation between advancing age and dilation of the temporal horns of the lateral ventricles, right lateral ventricle, and third ventricle in their population of cats but not between age and the presence of dilated olfactory recesses. 1 As discussed above, the olfactory recesses in the fetus are normally filled with CSF. In humans, they then regress progressively to be generally absent at the time of birth, 20,21 while in animals they progressively collapse and are empty of CSF contents in adult individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the intensity pattern of the dilated olfactory recesses was consistent with that of the remainder of the CSF-filled ventricular system, being markedly T2W hyperintense, T1W hypointense and suppressing on the FLAIR sequence in all patients. While one publication has described ipsilaterally reduced olfaction in one dog with hydrocephalus and unilateral olfactory recess dilatation, 1 this remains a single report and olfaction is in fact not routinely tested in small animals, due to the difficulty in evaluating this objectively, especially when olfaction is incomplete. 17 Furthermore, in the human literature, the presence of olfactory recess dilatation has not been found to be associated with any reduction in olfaction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations